INVESTMENT OPPORTUNITY SET, CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN - Aliyah, Siti (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This study aims to examine the effect of investment opportunity sets and corporate governance on company value. The population of this study is all commercial banks listed on the Indonesia Stock Exchange (IDX) for the period 2011-2017. The sampling technique is the purposive sampling method. The analytical method used in this study is linear regression analysis using SPSS 20.0 software. The results showed that the investment opportunity set had a positive and significant effect on firm value while the corporate governance mechanism had no effect on firm value.Â